Population structure of Pacific green turtles: a new perspective from microsatellite DNA variation - Roden, Suzanne E.; Horne, John B.; Jensen, Michael P.; FitzSimmons, Nancy N.; Balazs, George H.; Farman, Richard; Cruce Horeg, Jennifer; Hapdei, Jessy; Heidemeyer, Maike; Jones, T. Todd; Komoroske, Lisa M.; Limpus, Colin J.; et al. (Frontiers in Marine Science, 2023)
This study builds upon the current understanding of green turtle population genetic structure in the Pacific that has largely been based on mitochondrial DNA (mtDNA), by examining nuclear DNA (nDNA) diversity, regional connectivity, and male-mediated gene flow. A total of 1,111 nesting green turtle samples were analyzed with 10 microsatellite markers from 20 Pacific rookeries. Population differentiation (FST) was significant (p <0.05) in all but 8 of 190 pairwise rookery comparisons. Pairwise FST values and discriminant analysis of principal components (DAPC) revealed a defined East-West split consistent with mtDNA studies. Additionally, isolation-by-distance was evaluated with estimated effective migration surfaces (EEMS). The data indicated structure throughout the Pacific rookeries largely in agreement with stock structure defined by mtDNA studies, except for some areas on the Central American and Australian continental shelves, providing evidence of possible male-mediated gene flow. The series of analyses performed did indicate that male-mediated gene flow has likely occurred where breeding migration corridors of separate populations overlap with courtship areas. This may occur primarily along the margins of continents, including along Mexico and Central America in the East Pacific. Our study provides an ocean-wide baseline nDNA dataset for green turtle rookeries in the Pacific and reexamines the current thinking regarding the role of male turtles in the population dynamics of management units (MU) and to what extent nuclear gene flow occurs among designated MUs.